Intracellular and immune-response delays effects on the interation between tumor cells, oncolytic viruses and the immune system - Winnie Wanja, Chabaari (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.